Electricity Smart Metering in the Czech Republic Status and Future Challenges - Vaniš, Zdeněk; Jaklová, Martina L.; Moc, Miloslav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2011)
This work deals with technology and innovation management issues on the particular case of electricity smart metering in the Czech Republic. The popular literature on this topic is not reflecting on industries with high level of regulation in demand determination, which is the precise case of this industry. Positions of distribution network operators, technology suppliers, end-consumers and the regulatory players are analyzed. Comparison with other European countries is shown with market development predictions also taking part of the analysis. The outcome of this work reflects on the 2012 decision of the regulatory authority in the Czech Republic, which is to decide on a mandatory roll-out of this technology. This work presents the path towards this decision and discusses the potential outcomes.
Vedoucí práce: Martina L. Jaklová
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2011
Rok obhajoby 2011
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses